KNOWLEDGE, ATTITUDE, AND PRACTICE OF LABOR ANALGESIA IN ANTENATAL WOMEN IN AMALAPURAM: A CROSS-SECTIONAL OBSERVATIONAL STUDY. - Hasamnis, Varada; Shaik, Mohammed Safiya; Bhargavi, Kagita Vasudha (Student’s Journal of Health Research Africa, 2025)
Background Labor analgesia is crucial for managing labor pain, yet its awareness and acceptance remain low in many developing regions. This study aims to assess the knowledge, attitude, and practice regarding labor analgesia among antenatal women in Amalapuram, a rural area in India. Methods An observational cross-sectional study was conducted with 150 antenatal women aged 18-40 years attending the antenatal clinic at a tertiary care hospital. Data were collected using a structured questionnaire that assessed demographics, knowledge, attitude, and practice regarding labor analgesia. Statistical analysis was performed using Microsoft Excel 2016. Results Of the 150 women surveyed, 25% were aware of labor analgesia. The majority (62%) of the 112 unaware respondents expressed interest in learning more, primarily preferring to receive information during obstetric consultations (55%). Concerns regarding labor analgesia were mainly centered around safety (85.3%) and its potential impact on the baby (56%). Regarding attitudes, 76% of participants feared labor analgesia, and 92.6% believed healthcare providers should offer it. Only 30% expressed interest in opting for labor analgesia in future pregnancies, with 70% preferring a natural birth. Knowledge dissemination was largely limited to family and social media sources. Conclusion The study reveals a low awareness of labor analgesia among antenatal women in Amalapuram, with significant interest in learning more about it. Healthcare providers, especially obstetricians, should be proactive in educating women during the antenatal period to increase acceptance of pain relief methods, which could improve maternal comfort and birth outcomes. Recommendations To improve awareness and acceptance of labor analgesia, healthcare providers, particularly obstetricians, should actively educate antenatal women during early pregnancy visits. Addressing misconceptions, enhancing communication, and providing clear, accurate information about pain relief options can help increase utilization. Further studies should explore cultural factors influencing pain relief choices in diverse populations.